Targeted Nipple Areola Complex Reinnervation in Gender-affirming Double Incision Mastectomy with Free Nipple Grafting. Issue 4 (14th April 2022) - Gfrerer, Lisa; Winograd, Jonathan M.; Austen, William G.; Valerio, Ian L.
Abstract : Background: Restoration of breast sensation has become an important goal in autologous and implant-based breast reconstruction after cancer-related mastectomy. Although gender-affirming mastectomy with free nipple grafting (FNG) results in similar sensory deficits, chest reinnervation concepts have not been applied to this procedure. Methods: This article describes a novel technique to reinnervate the FNG in patients undergoing double incision gender mastectomy. Results: Our technique differs from previously described reinnervation techniques in several aspects: (1) the donor axon count is maximized by preserving the third to fifth lateral cutaneous nerves for coaptation to the nipple areola complex, (2) the reinnervation approach varies and is based on patient anatomy, (3) the distal graft or donor nerve is split into fascicles to increase the reinnervation zone, and (4) the split fascicles are coapted to the dermatosensory peripheral nerve elements of the dermis. Conclusion: Chest reinnervation is technically feasible in patients undergoing double incision gender mastectomy with FNG (please also see the video abstract).